PERAN BADAN PENELITIAN DAN PENGEMBANGAN KEMENTERIAN DALAM NEGERI DALAM MENGIMPLEMENTASIKAN INOVASI DAERAH SESUAI DENGAN PERATURAN PEMERINTAH NOMOR 38 TAHUN 2017 TENTANG INOVASI DAERAH - David Julianto Simanungkalit; Eko Prasojo (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2020)
This research aims to see and analyze how innovation policies are implemented by the Research and Development Agency of the Ministry of Home Affairs. This study uses a post-positivism paradigm with qualitative research methods. In-depth interviews and document studies were conducted to obtain the necessary data and information. The implementation, which is carried out from the leadership level to the subordinates and collaborating with various actors, is expected to be the main milestone in the implementation of regional innovation so that it is useful for improving people's welfare and regional independence. However, to improve the quality of the implementation of these regional innovation programs, it is still necessary to strengthen the role of the Research and Development Agency of the Ministry of Home Affairs including aspects of human resources, programs and budget. Keywords: implementation, innovation